Computer-Aided Cryptographic Proofs - Barthe, Gilles; Crespo, Juan Manuel; Grégoire, Benjamin; Kunz, César; Zanella-Béguelin, Santiago (3rd International Conference on Interactive Theorem Proving, ITP 2012, 2012)
EasyCrypt is an automated tool that supports the machine-checked construction and verification of security proofs of cryptographic systems, and that has been used to verify emblematic examples of public-key encryption schemes, digital signature schemes, hash function designs, and block cipher modes of operation. The purpose of this paper is to motivate the role of computer-aided proofs in the broader context of provable security and to illustrate the workings of EasyCrypt through simple introductory examples.